Hypnolearning Reduces Mathematics Learning Anxiety in Elementary School - Oman Suryaman (UM Purwokerto Press, 2023)
Mathematics is often assumed to be an unpleasant subject, so that sometimes anxiety arises and there is even a fear of learning mathematics. Efforts are needed to reduce anxiety and fear of learning mathematics by providing positive and pleasant suggestions for learning mathematics through the application of Hypnolearning. The population in this study were fifth grade students at SD Negeri 1 Lengkong Kuningan. The purpose of this research is to prove empirically the application of hypnolearning to reduce anxiety. This research is important to carry out because it can be used as material for consideration in the healing process of anxiety disorders for therapists. This study uses experimental research. Research data obtained from observation, interviews and questionnaires. In the observation technique, researchers come to observe the learning process. Furthermore, researchers conducted interviews and gave questionnaires to students. The research was conducted by providing Hypnolearning to students. Data obtained from pretest and posttest.